Profile of Endometrial Cancer Patients in the Third Referral Hospital in Surabaya based on Known Risk Factors - Nihal Sofyan; I Ketut Sudiana; Brahmana Askandar (Biomolecular and Health Science Journal, 2020)
Introduction: Endometrial cancer is a malignant tumor of primary endometrial epithelium that placed as the sixth most common cancer in women worldwide. The exact cause of it is still unknown although there are several risk factors has been well studied and the incidence rate is increasing every year. The aim of the study is to describe the profile of endometrial cancer patients in third referral hospital in Surabaya based on known risk factors.Methods: We collected data retrospectively through the medical record of outpatients with endometrial cancer diagnosis from January-December 2016. A total of 120 patients were collected and only 95 patients who meet the inclusion criteria. Data about age, age of menarche, status of menopause, parity, Body Mass Index (BMI), history of disease, and family history of cancer were extracted then presented descriptively.Results: From 95 patients, the largest distribution were age 51-60 years old (47,37%), and was diagnosed mostly in women with parity ≤2 (47,37%), postmenopausal status (61,05%), age of menarche ≥ 12 (85,26%), and normal weight (35,79%). Most of patients didn’t have either any history of disease (57,89%) or family history of cancer (89,47%).Conclusion: Most of the endometrial cancer patients in Dr. Soetomo General hospital Surabaya were women aged 51-60 years old with postmenopausal status, age of menarche ≥ 12 years old, number of parities ≤2, and normal weight. The majority of them were also found to have no history of disease and family history of cancer.